INTERNALISASI NILAI-NILAI PENDIDIKAN KARAKTER DI MADRASAH - Isnaini, Muhammad (Institut Agama Islam Negeri Imam Bonjol Padang, 2013)
Character education is a positive offer in the eradication of moral crises which particularly emerged in our students. Therefore, the internalization of values of character education in the educational institution is a must. As an Islamic education institution in Indonesia, the existence of Boarding school is considered to be able to develop values of character education which may be done through formal or non-formal curriculum. This is so because since its early existence, Boarding school has delineated its distinctive feature which is different from the other common types of education. Here, the implementation of character values have been integrated (within large portion) in the religious subjects.Copyright © 2013 by Al-Talim All right reservedDOI: 10.15548/jt.v20i3.41